1996
DOI: 10.1089/tmj.1.1996.2.25
|View full text |Cite
|
Sign up to set email alerts
|

The University of Texas Medical Branch— Texas Department of Criminal Justice Telemedicine Project: Findings from the First Year of Operation

Abstract: Preliminary review of the data indicated favorable care outcomes, and initial economic analyses suggested that telemedicine is likely to be cost-effective in this environment. The project will be continued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 2 publications
0
40
0
Order By: Relevance
“…Comparing reported satisfaction levels across studies in different specialties is difficult because of variation in research methodology, and the failure to report on important study details. Although a large number of studies in this review reported data from a range of specialties, 29,32,54,57,58,61,63,65,70,75,87,93,106 differences between groups in terms of reported satisfaction were generally not examined. Small sample size prohibits the analysis of satisfaction across subgroups in several of these multispecialty studies.…”
Section: Factors That Mediate Patient Satisfaction With Telemedicinementioning
confidence: 99%
See 1 more Smart Citation
“…Comparing reported satisfaction levels across studies in different specialties is difficult because of variation in research methodology, and the failure to report on important study details. Although a large number of studies in this review reported data from a range of specialties, 29,32,54,57,58,61,63,65,70,75,87,93,106 differences between groups in terms of reported satisfaction were generally not examined. Small sample size prohibits the analysis of satisfaction across subgroups in several of these multispecialty studies.…”
Section: Factors That Mediate Patient Satisfaction With Telemedicinementioning
confidence: 99%
“…Two studies with sample sizes of 585 and 495 patients did not provide a comparison of satisfaction data across specialties. 29,54 One study which investigated medical specialty as an intervening variable among 221 prison patients found no differences between six specialties (pulmonary, plastic surgery, gastroenterology, psychiatry, general surgery, and hand problems. 87 A similar finding was reported by Callahan et al, 32 who compared the satisfaction ratings of 34 mental health patients with those of 59 nonmental health patients receiving telemedicine.…”
Section: Factors That Mediate Patient Satisfaction With Telemedicinementioning
confidence: 99%
“…[25] This avoids additional costs such as transportation and security measures achieving good satisfaction among the users. [26][27][28] Several studies were performed to help prisons and health services in producing a model for partnership in the delivery of health care in penal establishments. They included models whereby local and Sanitary System augment prison health care through telemedicine.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown acceptance of this technology by both prisoners and practitioners and reasonable cost-effectiveness. 46,47 This technology has not been studied yet in incarcerated children. Can it be demonstrated that standards of care delivered by telemedicine for the incarcerated child population are at least equivalent to those accepted in the local community?…”
Section: Incarcerated Youthmentioning
confidence: 99%